Solve the following equation: (4x – 10) + 5 = x – 11 %0D%0A(1 point)%0D%0AResponses%0D%0A%0D%0A11%0D%0A11%0D%0A%0D%0A6%0D%0A6%0D%0A%0D%0A–11%0D%0A–11%0D%0A%0D%0A–6%0D%0A–6

1 answer

To solve the equation (4x - 10) + 5 = x - 11, we need to simplify and isolate the variable x.

First, let's simplify the left side of the equation:
(4x - 10) + 5 = x - 11

Combine like terms:
4x - 10 + 5 = x - 11

Simplify further:
4x - 5 = x - 11

Now, let's isolate the variable x by subtracting x from both sides of the equation:
4x - x - 5 = x - x - 11

Simplify:
3x - 5 = -11

Next, let's isolate the variable x by adding 5 to both sides of the equation:
3x - 5 + 5 = -11 + 5

Simplify:
3x = -6

Finally, divide both sides of the equation by 3 to solve for x:
3x/3 = -6/3

Simplify:
x = -2

Therefore, the solution to the equation is x = -2.